Processo de trabalho na estratégia saúde da família após a implantação do Programa Mais Médicos - Santana, Lívia Leal Lopes de (2017)
Study on the work process in the Family Health Strategy, after the implantation of the more doctors program. It presents as guiding questions: how does the work process in the Family Health Strategy occur after the implantation of the More Doctors Program in a municipality in Bahia? How are the constituent elements of the health work process presented in the Family Health Strategy in a municipality in Bahia? What are the facilities, difficulties and challenges after the implantation of the More Doctors Program for the work process in the Family Health Strategy in a municipality in Bahia? The general objective is to analyze the work process in health in the Family Health Strategy, after the implantation of the more doctors program in a municipality of Bahia; And specific objectives: to describe the constitutive elements of the health work process in the Family Health Strategy in a municipality of Bahia; To discuss the facilities, difficulties and challenges encountered in the teamwork of the Family Health Strategy after the implantation of the more doctors program in a municipality in Bahia. This is a case study with a qualitative approach,whose project was submitted to the Research Ethics Committee of the UEFS and approved according to opinion number: 1.530.791. The data collection, carried out from June to July 2016, occurred through a semi-structured interview with twelve health workers and ninefamily health unit users analyzed; document analysis; and systematic observation. The empirical material was analyzed using the content analysis technique proposed by Bardin (2011).The care model is centered on the care of the community through clinical procedures and consultations to the detriment of activities aimed at health promotion. The actions developed are based on ministerial programs and the fragmentation of care, where each worker performs his actions individually, with few moments of interaction between the teams, especially the Oral Health Teams. Regarding the implantation of the program more doctors, no changes were found in the work process of other health workers, but the adaptation of foreign physicians to a biological health system.However, it was noticed the recognition of the community and the majority of the workers regarding the differentiated care of the doctors of the program who started to stay in the family health unit full-time, having only an employment relationship. Also, difficulties were not recognized that prevented care on behalf of the language of doctors. Among the difficulties, it should be noted that the program has not yet contributed to the advancement of the family health unit infrastructure, being found problems regarding the lack of materials, instruments and inputs important for the continuity of work, as well as the of the users, for the accomplishment of educative activities in detriment to the assistencialist practices. In this sense, the great challenge is the reformulation of the health work process, so that the core of the professional activity is centered on the users, breaking the paradigm of individualized actions, with a view to strengthening teamwork.